2007
DOI: 10.1002/ajmg.b.30463
|View full text |Cite
|
Sign up to set email alerts
|

Association of a serotonin receptor 2A gene polymorphism with cognitive functions in patients with schizophrenia

Abstract: The aim of this study was to investigate the association between the T102C polymorphism on the 5HT2A gene and cognitive function as well as clinical manifestations in patients with schizophrenia. Eighty-two outpatients with schizophrenia participated in this study. The Brief Psychiatric Rating Scale (BPRS) was used to assess the severity of each patient's symptoms. In order to evaluate their short-term attention capacity, a Digit Span Test was used. The Continuous Performance Test (CPT) was used to test the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 14 publications
3
8
1
1
Order By: Relevance
“…Specifically, antisaccade latencies were significantly longer in C allele homozygotes than in T allele carriers. This finding is congruent with previous findings obtained using other executive tasks (e.g., Becker et al 2004;Bjork et al 2002;Üçok et al 2007;Vyas et al 2012) and suggests that inhibition of a prosaccade response was impaired or more effortful in C allele homozygotes relative to T allele carriers. At the same time, prosaccade latencies were not significantly affected by rs6313 genotype (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, antisaccade latencies were significantly longer in C allele homozygotes than in T allele carriers. This finding is congruent with previous findings obtained using other executive tasks (e.g., Becker et al 2004;Bjork et al 2002;Üçok et al 2007;Vyas et al 2012) and suggests that inhibition of a prosaccade response was impaired or more effortful in C allele homozygotes relative to T allele carriers. At the same time, prosaccade latencies were not significantly affected by rs6313 genotype (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The C allele of rs6313 is associated with low gene expression. Homozygosity for the C allele (i.e., C/C genotype) is associated with characteristic features of several psychiatric disorders, in particular, impaired cognitive function (e.g., Becker et al 2004;Üçok et al 2007;Vyas et al 2012). For example, previous work has found that individuals with the C/C genotype make more errors than those with the T/_ genotypes (i.e., T/C or T/T genotypes) on a test of behavioral control (Bjork et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Significant reduction in cortical 5-HT2A receptor binding has been observed in patients with Asperger's syndrome and has been related to abnormal social communication (Murphy et al, 2006). In addition, numerous studies have reported associations between HTR2A polymorphisms and cognitive impairment and memory (Uçok et al, 2007;Hasselbalch et al, 2008;Sigmund et al, 2008;Wagner et al, 2008;Alfimova et al, 2010). Our results contribute evidence supporting the involvement of 5-HT2A receptor alterations on cognitive impairment in ASD patients.…”
Section: Genessupporting
confidence: 77%
“…The Maudsley EOS study showed an association of the serotonin receptor 2A gene (5HTR2A) with attention and executive functioning in EOS probands and their first-degree relatives [ and their first-degree relatives. Manuscript Submitted], which supports an earlier study in adult-onset patients [73]. Further similar investigations using a family-based design [74] may help us to better understand the mechanisms underlying the transition to psychosis in apparently healthy siblings of schizophrenia patients who have not passed the period of risk for developing the illness.…”
Section: Editorialsupporting
confidence: 70%